Escaping the Low-Growth Trap : Guinea-Bissau Country Economic Memorandum - World Bank (World Bank, Washington, DC, 2020)
Guinea-Bissau’s massive economic potential has not so far translated into better livelihoods for its population. Growth per capita has averaged less than 1 percent per year over 2000-2019. This chapter provides an in-depth analysis of the factors behind the economic stagnation. An interplay of three constraints have impeded sustained high growth. First, the low and volatile growth performance is linked to fragility and political instability, which, together with a poorly diversified economy, with raw cashew nuts accounting for 95-98 percent of export earnings, help explain the stop-go growth cycle. Second, human capital accumulation remains low. An acute shortage of a skilled workforce is a major constraint to inclusive growth. The education system is marked by alarmingly low levels of learning. Third, private investment is particularly low—the second lowest in Africa. Years of underinvestment in infrastructure, energy, and human capital are holding the country back from achieving strong, enduring and inclusive growth. The chapter concludes by highlighting how the COVID-19 crisis exacerbates these constraints and discusses areas that could support sustainable growth. The chapter is organized as follows: section 1.1 presents a brief overview of the political and social context. Section 1.2 puts recent growth into historical and comparative perspective. Section 1.3 presents analysis that helps explain the low-growth trap and identifies possible areas that Guinea-Bissau could pursue to escape this trap. Finally, Section 1.4 discusses the economic impact of COVID-19 and potential pathways to recovery.